Assessment of dependence and risk of patients undergoing hemodialysis in a public hospital in the year 2016 and 2017 (Research, Society and Development, 2022)
Objective: To classify the risk and degree of dependence of patients undergoing hemodialysis in a public hospital in the state of Mato Grosso do Sul. Methods: Cross-sectional study carried out in a hemodialysis unit from September 2016 to April 2017. Data were collected, with structured interview, analysis of medical records and application of the instrument Categorización User Según Dependency y Riesgo, in hemodialysis units (CUDYR-DIAL). Data analysis was performed using simple descriptive statistics. Results: Sample composed of 27 patients, the majority were male with a mean age of 61.22 years.  The categorization showed high risk and partial self-sufficiency (51.9%). As for dependence, most required basic care, however, 88.9% needed psychosocial and emotional support. Regarding risk, it was found that 81.5% of patients were characterized as high risk and thus required strict control of vital signs, care with vascular and skin accesses, and medication administration during the hemodialysis section. Conclusion: Patients demand complex and risky care activities, and they need psycho-emotional support.